Facile enantioselective synthesis of (S)-N-(5-chlorothiophene-2-sulfonyl)-beta,beta-diethylalaninol via proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination of aldehyde - Rawat, Varun; Chouthaiwale, Pandurang V.; Chavan, Vilas B.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A high-yielding enantioselective synthesis of the bioactive (S)-N-(5-chlorothiophene-2-sulfonyl)beta,beta-diethylalaninol (1), a Notch-1-sparing gamma-secretase inhibitor metabolite (with EC50 = 28 nM) effective in reduction of All production in vivo, has been realized starting from readily available 3-pentanone. The key steps of the synthesis are proline-catalyzed alpha-aminooxylation and alpha-amination of aldehyde: the latter contributing an overall yield of 45.2% and 98% ee. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; alpha-Aminooxylation; Alzheimer's disease; Amino alcohol; Proline

Fluoride-assisted synthesis of 1,4,5,6-tetrahydropyridazines via [4+2] cyclodimerization of in situ-generated azoalkenes followed by a C-N bond cleavage - Shelke, Anil M.; Suryavanshi, Gurunath (Organic Letters, 2016)
An unexpected CsF-assisted C-N bond cleavage was exploited to synthesize highly functionalized and biologically important 1,4,5,6-tetralrydropyridazine derivatives from alpha-halo N-acylhydrazohes in excellent yields. The extrusion of nitrogen and the [4 + 2] cycloaddition between in situ-generated azoalkenes is a key reaction in the process. The identified methodology is suitable for synthesizing a wide variety of analogues of tetrahydropyridazines, which are prevalent in many medicinally important small molecules. The reaction conditions are mild, high-yielding, and amenable for the gram scale.

Formal synthesis of pinolide via L-proline-catalyzed sequential alpha-aminooxylation, horner-wadsworth-emmons olefination and sharpless asymmetric dihydroxylation - Shelke, Anil M.; Suryavanshi, Gurunath (Tetrahedron-Asymmetry, 2016)
A convergent, formal enantioselective synthesis of pinolide, a new nonenolide, has been achieved with high enantiomeric purity (99% ee) starting from readily available raw materials. The main highlight of the synthetic strategy is the application of L-proline catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination of an aldehyde, Sharpless asymmetric dihydroxylation and Steglich esterification as the key steps for the construction of a key chiral intermediate of the target molecule. (C) 2016 Elsevier Ltd. All rights reserved.